Pengaruh Promosi dan Distribusi Terhadap Kepuasan Pelanggan Pada PT Tiga Serangkai Internasional Cabang Bandung - Anang Martoyo; Fajar Mahardika (Jurnal Pemasaran Kompetitif, 2020)
The objectives of the research are to know the responses about promotion, distribution, customer satisfaction, and customer trust, also to analyze the influence of promotion and distribution to customer satisfaction and its implication on customer trust. The population in this study is PT. Tiga Serangkai International in the reater Bandung Region. The research method used in this research is descriptive and verification research method with a sample size of 90 respondents, data collection by interview using a questionnaire, observation and literature. Sampling technique using the "Disproportionate Starfied Random Sampling" method. Data analysis method used is path analysis. The results showed that promotion and distribution simultaneously influence customer satisfaction, partially promotion and distribution have a significant effect on customer satisfaction. Promotion gives an influence on customer satisfaction by 16%, while distribution gives an effect of 75.9%. The contribution of promotion and distribution variables to customer satisfaction is 73.7%, the remaining 26.3% is the contribution of the variables not included in the study